Modification of essential factors mediating post-translational processing for high-quality protein expression in Penicillium - Demin Guo; Shengfang Zhao; Jie Chen; Shuhui Han; Yangtao Li; Yu Chen; Shengbiao Hu; Yibo Hu (Engineering Microbiology)
The formation of mature proteins requires complex post-translational modification and processing. Efficient post-translational processing machinery is beneficial for the high-quality expression of proteins. To comprehensively evaluate the role of post-translational mediating factors (PTMFs) in protein synthesis, two reporter strains expressing a homologous protein, Amy15A, and a heterologous protein, TaEG, were constructed in Penicillium oxalicum. Three PTMFs including a conserved basic leucine zipper transcription factor, HacA; an endoplasmic reticulum chaperone-binding protein, BipA; and a protein disulfide isomerase, PdiA, were individually overexpressed in the both reporter strains. The findings showed that overexpression of these PTMFs enhanced the enzymatic activity of both homologous and heterologous proteins. However, sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis revealed that, upon overexpression of the PTMFs, heterologous protein secretion remained stable or slightly increased, whereas that of homologous proteins remained unchanged or decreased. Neither the vegetative growth rate nor reporter transcription levels accounted for these variations in protein production or enzymatic activity. Conclusively, this study suggests that PTMFs play a positive role in protein expression and can be leveraged to optimize filamentous fungal chassis cells in the future.